Phosphate-Based Self-Immolative Linkers for the Delivery of Amine-Containing Drugs - Đud, Mateja; Tichotová, Markéta; Procházková, Eliška; Baszczyňski, Ondřej (Molecules (Basel, Switzerland), 2021)
Amine-containing drugs often show poor pharmacological properties, but these disadvantages can be overcome by using a prodrug approach involving self-immolative linkers. Accordingly, we designed l-lactate linkers as ideal candidates for amine delivery. Furthermore, we designed linkers bearing two different cargos (aniline and phenol) for preferential amine cargo release within 15 min. Since the linkers carrying secondary amine cargo showed high stability at physiological pH, we used our strategy to prepare phosphate-based prodrugs of the antibiotic Ciprofloxacin. Therefore, our study will facilitate the rational design of new and more effective drug delivery systems for amine-containing drugs.
Keywords: amine-containing drugs; léčivé přípravky; Pharmaceutical Preparations; Lactic Acid; Prodrugs; 31P-NMR spectroscopy; phosphate-based linkers; Drug Delivery Systems; self-immolative linkers; aminy; antibakteriální látky; ciprofloxacin; Amines; prodrugs; Anti-Bacterial Agents; lékové transportní systémy; Ciprofloxacin; Hydrogen-Ion Concentration; prekurzory léčiv; fosfáty; koncentrace vodíkových iontů; kyselina mléčná; Phosphates